Combination of Genome-Wide Association Study and QTL Mapping Reveals the Genetic Architecture of Fusarium Stalk Rot in Maize - Liu, Shuangshuang; Fu, Jingxiao; Shang, Zhigang; Song, Xiyun; Zhao, Meiai (Frontiers in Agronomy, 2021)
Stalk rot causes significant yield loss in maize worldwide. The breeding of resistant variety is a potential way to effectively control the disease. This study aims to dissect resistance genes for maize stalk rot caused by Fusarium graminearum using an integrated gene mapping method. A diversity panel of 165 inbred lines and an F2 population from the hybridization of CDMA66 and Huangzao 4 were used as materials. The 165 inbred lines were clustered into four subgroups, of which tropical materials are in the majority. Through combining disease severity index (DSI) and single nucleotide polymorphisms (SNPs) of Maize 50K chip and 20K, genome-wide association analysis (GWAS) revealed 34 SNPs that were significantly associated with stalk rot in maize (P < 0.001). These SNPs were distributed on chromosomes 1, 3, 4, 6, 8, and 10, of which the loci on chromosomes 4 and 8 were confirmed by the mapped QTLs for stalk rot. Finally, candidate genes were identified including GRMZM2G082709 which encoded NAC domain-containing protein and thioredoxin reductase (GRMZM5G841142). However, LRR receptor-like serine/threonine-protein kinase (GRMZM2G080041) was down-regulated after inoculation. These SNPs and candidate genes identified would provide essential information for resistant gene cloning and molecular breeding of anti-stalk rot variety in maize.